Fetal Alcohol Syndrome: a complex case of teratogenic effects of maternal alcohol consumption and clinical managment - Koziej, Sylwia; Kowalczyk, Emilia; Borkowska, Joanna; Bajorek, Julia (Quality in Sport, 2024)
Introduction and purpose Maternal alcohol consumption during pregnancy is a well-documented risk factor for adverse fetal outcomes, encompassing a spectrum of disorders known as Fetal Alcohol Spectrum Disorders (FASD). Fetal Alcohol Syndrome (FAS), the most severe form of FASD, manifests with craniofacial anomalies, growth retardation, neurological deficits, and cognitive impairments, imposing lifelong challenges on affected individuals. This article presents a case report of a 4-week-old female newborn with suspected Fetal Alcohol Syndrome, highlighting the clinical complexities and diagnostic challenges associated with FAS. The infant exhibited characteristic dysmorphic features and cardiac abnormalities, underscoring the diverse spectrum of health issues linked to maternal alcohol consumption. Conclusion A presented case report illustrating the clinical complexities of FAS underscores the importance of early recognition and multidisciplinary management. Early identification of FAS is imperative to mitigate long-term outcomes, emphasizing the importance of a multidisciplinary and holistic approach to clinical care. Strategies for addressing maternal alcohol consumption include targeted education, preconception counseling, and innovative therapeutic modalities. This case report underscores the need for ongoing research and collaborative efforts to reduce the prevalence and impact of FASD on affected individuals and society.